Production of extracellular proteases by Mucor circinelloides using D-glucose as carbon source / substrate - Andrade,Vânia Sousa (2002)
Recently, some Mucorales species have been reported as protease producers. The production of extracellular proteases by Mucor circinelloides using glucose as substrate was studied. Experiments were carried out with different D-glucose concentrations (40, 60 and 80 g/L). Biomass, pH and protease activity were determined. Although biomass production had reached best yields for the medium containing D-glucose in a concentration of 80 g/L, the enzymatic production was higher when the substrate concentration was reduced to 40 g/L. The yield factor for product on cell growth and the yield factor for product on carbon substrate were higher when the microorganism grew in medium containing 40 g/L glucose. The kinetics parameters suggest that this strain seems to be promising as an alternative microorganism for protease production.